Influence of the Hydrophobic–Hydrophilic Nature of Biomedical Polymers and Nanocomposites on In Vitro Biological Development. Issue 12 (10th November 2017) - Torres, Elena; Vallés‐Lluch, Anna; Fombuena, Vicent; Napiwocki, Brett; Lih‐Sheng, Turng
Abstract: In this work, cell viability, proliferation, and morphology are studied on two pairs of polymers used in the biomedical field that have similar chemical natures but differ in hydrophobicity. On the one hand, hydrophobic polyester poly(ε‐caprolactone), is modified by blending with poly(lactic acid). On the other hand, the hydrophilic acrylate poly(2‐hydroxyethyl methacrylate) (PHEMA), is copolymerized with ethyl methacrylate (EMA) at a ratio of 50/50 wt.% P(HEMA‐ co ‐EMA). These two polymers are used as neat resins or combined with hydroxyapatite (HA) nanoparticles and halloysite nanotubes (HNTs) to enhance cell attachment and mechanical properties. Cell proliferation is greater on moderately hydrophobic materials at the initial stage, with cells showing a round shape and aggregating in clusters. However, over longer culture periods, cell proliferation is more advanced on more hydrophilic surfaces, where cells spread out with a flatter shape. Improvement of cell viability is observed with the addition of HA and HNTs. Abstract : Studying the biological development and compatibility, this original research shows, as at the initial stage, the cell proliferation is greater on hydrophobic materials (poly(ε‐caprolactone)‐poly(lactic acid)), but over longer stage, cell proliferation is greater on hydrophilic materials (poly(2‐hydroxyethyl methacrylate)‐ethyl methacrylate). This effect is improved with the creation of composites using hydroxyapatite and halloysite nanotubes.